Variational Solutions in Orbital Free Density Functional Theory - Ryley, Matthew S (2020)
This work focusses on testing and developing methods to find solutions to the variational problem at the heart of orbital free density functional theory (OF-DFT). OF-DFT is an inherently linear scaling quantum chemical method which can, in theory, be used to simulate systems with millions of atoms. However, there is a limited choice of OF-DFT codes which are suitable for the development of the theory for chemical systems. In this work we compare and contrast three methods: the Lopez-Acevedo scheme[1]; the Chan, Cohen and Handy Scheme[2,3] (CCH); and the trust-region image method (TRIM) scheme[4]; We find that the scheme developed in this work --- the TRIM scheme --- offers the most efficient methodology for converging the energy for a wide range of functionals in an all electron context for finite chemical systems.